EFFECTS OF CEFMENOXIME ON BLOOD COAGULATION, PLATELETS, AND FIBRINOLYTIC SYSTEMS - ITO, KUNIHIKO; NODA, KATSUMI; KOIKE, SHIGEFUMI; HAYASAKI, MOTOKI; MATSUMOTO, KOJI (CHEMOTHERAPY, 1986)
Cefmenoxime (CMX), a cephem antibiotic with a methyltetrazole group, was evaluated for its effects on the bleeding tendency. Subjects without hemorrhagic dispositions were selected from surgical in-patients in the field of gynecology and obstetrics. They were given 1 or 2g of CMX by intravenous drip infusion twice daily for 7 days beginning on the day of surgery. Some of the patients given a daily dose of 4g CMX received a single dose of 30mg of vitamin K2, too, by i. v. drip on the day of surgery. Tests on the bleeding tendency were carried out before and after the 7-days administration with CMX. The examined items were as follows: thromboelastogram (r, k, and ma values), coagulation time (prothrombin time, PT; thrombotest, TT; hepaplastintest [normotest], HPT), quantity of coagulation factors (prothrombin, fibrinogen), bleeding time (BT), platelet count, platelet aggregation activity (aggregation reagents: ADP, collagen, epinephrine), and fibrinolytic activity (fibrin and fibrinogen degradation products, FDP; plasmin value; streptokinase-activated plasmin value). Results: 2g/day of CMX caused no statistically significant changes of the data in the direction of increased bleeding tendency, while in the group given 4g daily, PT, TT, and BT were slightly but significantly prolonged, although no significant changes were found in other parameters. Single injection of vitamin K2 could prevent the prolongation of coagulation time (PT, TT). Clinical hemorrhage did not occur in any patient. These results obtained should suggest that 4g CMX/day can be safely given for a week or so to patients in fairly good condition without vitamin K deficiency, but, when the drug is given to patients on parenteral alimentation, to the aged, or to those in poor conditions, vitamin K should be given as well to ensure safety.